MUHAMMED B. ABDULLAH CELIZÂDE VE KELAMI GÖRÜŞLERI - SALIHI, SHWAN FETHULLA RİDHA (Fırat Üniveristesi, 2022)
Bu çalışma Muhammed b. Abdullah Celîzâde'nin kelam görüşlerini konu edinmektedir. Celîzâde ilim ortamlarında ve özellikle de son dönem kelam fırkalarında açıklamaları, yorumları ve eleştirileriyle meşhur olan alimlerden birisidir. O, İlkeleri ve İslami değerleri korumakla birlikte büyücülüğü reddederek ülkelerin gelişmesini çağdaşlaşma ve modern ilimler ve çağdaş yapılardan faydalanmayı amaçlayan modernleşme akımının yöntemini izleyen bir alimdir. Bu çalışmada, görüşleri eleştirme ve söylenen her şeyi kabul etmemeyi bir metot olarak ortaya çıkaran metinleri çözümlerken Muhammed Celîzâde'nin kelam görüşlerini açıklamaya çalıştım. Bu çalışmada Celizade'nin ıslahatçı yönüne işaret edilmiştir. Yaşadığı dönemde Kur'an'ın yönlendirmesine aykırı olarak insanların düşüncelerine tasallut eden ve din adı altında mallarına çökmeye çalışan sofilerin görüşlerindeki hurafelere karşı oluşuna değinilmiştir. İşaret ettim çözmek için Birçok sorunasözlü, sosyal ve bilimselve entelektüe ve inandığını açıkla, sonuca götürse bile. Ona zarar çünkü savaştıbirçok inanç Şeriata aykırıİslam ve Etikve genel görgü kuralları.

This study discussed the personality of Muhammad Abdullah Galizadeh. Where his speech views, and his additions were explained. The scholar Muhammad Jalizadeh is one of those in-depth who had contributions, additions, and criticism of some of the concepts that are well-known among the scholars, especially the later scholars of theological sects. This study also showed the thought of Mullah Muhammad Galizadeh and his reformist vision in his life, and the approach of the modernist trend, which calls for contemporary and benefit from modern sciences and administrative systems that advance the country while preserving Islamic principles and values and rejecting sorcery. This study showed the verbal opinions of Muhammad Galizadeh with the analysis of its texts represented in criticizing opinions and not accepting everything that was said. This study also showed the aspect of doctrinal reform at Mullah Galizadeh, due to the spread in his time of myths and opinions that contradict the Qur'an and Sufi ideas, from the sheikhs' domination of people's minds and the exploitation of their money in the name of religion. And his rejection of imitation, especially among the scholars. This study referred to the treatment of many doctrinal, verbal, social, scientific and intellectual problems. Where this study indicated that Muhammad Galizadeh announced what he believed in, even if the situation would harm him, because he fought many beliefs that contradict Islamic law, morals, and public morals.
Fundamental Islamic sciences department the department of the kolam
Keywords: Din